2018
DOI: 10.1002/elps.201800284
|View full text |Cite
|
Sign up to set email alerts
|

Detection of non‐small cell lung cancer cells based on microfluidic polarization microscopic image analysis

Abstract: In early diagnosis of lung cancer, a polarization microscopy is a powerful tool to obtain the optical information of biological tissues. In this paper, a new microfluidic polarization imaging and analysis method was proposed for the detection and classification of cancer‐associated fibroblasts and the two kinds of non‐small cell lung cancer cells, A549 and H322. A polarizing microscopy system was constructed based on a commercial microscope to obtain 3*3 Mueller matrix of cells. Based on the Muller matrix deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Rossi et al showed that CD4 and CD8 T lymphocytes can be differentiated by their scattered light due to biophysical property differences [203]. Polarization microscopy can also be conjugated with machine learning for the detection and classification of non-small-cell lung cancer cells without any staining [204].…”
Section: Cell Counting and Classificationmentioning
confidence: 99%
“…Rossi et al showed that CD4 and CD8 T lymphocytes can be differentiated by their scattered light due to biophysical property differences [203]. Polarization microscopy can also be conjugated with machine learning for the detection and classification of non-small-cell lung cancer cells without any staining [204].…”
Section: Cell Counting and Classificationmentioning
confidence: 99%
“…Quadratic discriminant analysis is used in the classification and differentiation of dissimilar types of label-free tumor cells [ 35 ]. LR-based linear classifiers use microfluidic imaging and analysis to capture and isolate cancer-related fibroblasts and two different cell types of lung cancer [ 36 ]. A decision tree can help classify label-free cancer cells in blood with continuous flow in microfluidic channels.…”
Section: Systematic Descriptionmentioning
confidence: 99%
“…However, recent research in related areas has applied machine learning more generally to microfluidic platforms. For example, Wang et al (2018) developed a singlechannel microfluidic device and used polarization microscopy to classify CAFs and two different non-small cell lung cancer cell lines, A549 and H322, via logistic regression and gradient descent with regularization. Their classification algorithm achieved 66.7% accuracy.…”
Section: Chen Et Al 2017mentioning
confidence: 99%